A Model to Identify the Potential Target for Leveraged Buyout - Hermawan, Devina; Tanuwijaya, Elaine; Aditama, Jonathan; Kusno, John Iwan; Teja, Adrian (Jurnal Keuangan dan Perbankan, 2022)
This study aims to find a model based on agency theory to identify the target firms of leveraged buyout (LBO) transactions one year ahead. The likelihood of a firm being a target in an LBO transaction is estimated using logistic regression. The dependent variable is defined as one for the LBO target and zeroes otherwise. The independent variables are a firm's financial characteristics related to agency problems: leverage, tangible assets, free cash flow, market-to-book value ratio, profitability, and revenue growth. The sample is public-to-private LBO transactions in the United States from 2009 to 2019. We find that a firm with high leverage and free cash flow is more likely to become an LBO target. The findings are consistent with the agency theory. The management uses firm high free cash flow to gain more debt to pursue their benefits which is detrimental to shareholders' interest. Contrary to previous research, the firm's tangible asset does not increase the likelihood of becoming an LBO target.